The Perceptions of Nursing Students About the COVID-19 Pandemic - Ayse Sonay Turkmen; Nejla Canbulat Sahiner; Mehtap Pekesen (Galenos Publishing House, 2021)
Objective:This study was conducted to assess the perceptions of nursing students about coronavirus disease 2019.Method:The study was conducted in a cross-sectional descriptive method. The sample group consisted of 209 students who were available online, volunteered to participate in the study, and filled out the questionnaire. Data were collected with a questionnaire and the Pandemic Scale. The data were evaluated using Statistical Package for the Social Sciences software 21.0 with descriptive statistics, chi-square, t-test, analysis of variance, and Bonferroni test in further analysis, while p < .05 was the CI.Results:In this study, 81.8% of the students were girls and 97.6% were single. The rate of students who or whose relative was diagnosed with coronavirus disease 2019 was 7.2%, the rate of students who wore a mask to avoid coronavirus disease 2019 contamination was 98.1%, the rate of students who paid attention to social distancing was 96.7%, and the rate of students who used hand disinfectant was 77%. It was determined that the students' average scores from the Pandemic Scale were 172.55 ± 21.90. A significant difference was found in the conspiracy and environment sub-dimensions of the coronavirus disease 2019 causes dimension in the comparison of the students' mean scores from the sub-dimensions of the Pandemic Scale by their grade. A positive significant correlation was found between age and conspiracy sub-dimensions (p < .01).Conclusion:It was observed that some of the sub-dimensions of the Pandemic Scale had positive and negative relationships with each other. This shows that students should be supported with accurate information about coronavirus disease 2019 and in complying with personal avoidance measures.